Legal Protection of Notaries Who Are Suspected (Study of Decision N0.17/PID. PRA/2022/PN. Mdn) - Hoiriyah, Hoiriyah (Universitas Islam Malang, 2023)
Abstract: Legal protection for notaries who are indicated criminal acts in connection with the authentic deed they make. Public prosecutors and judges generally apply certain articles in the Criminal Code (KUHP) to drag notaries into criminal cases because Law Number 2 of 2014 concerning Notary Positions (UUJN) does not contain concepts and systems at all Notary criminal liability. The notary office is a public office because notaries are appointed and dismissed by the government. Notaries perform state duties and the deed they make, namely minuta (original deed), is a state document. In Indonesia, a notary is referred to as a General Officer because he is numbered and dismissed by the general power (government) and is given the authority and obligation to serve the public in certain matters, and therefore he participates in exercising the authority of the government. conclusion that legal protection of Notaries is dalam carrying out the duties of his office as a General Officer can be seen in several instruments that reflect notary privileges, including the right of denial, the obligation of denial and the right of exclusivity when summoned for questioning information by investigators, public prosecutors or judges, which must be with the approval of the Regional Notary Honor Council. Keywords: Legal protection, Notary, Criminal act, Authentic deed, Legal consequences